2010
DOI: 10.1186/1471-2164-11-398
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the equine skeletal muscle transcriptome identifies novel functional responses to exercise training

Abstract: BackgroundDigital gene expression profiling was used to characterize the assembly of genes expressed in equine skeletal muscle and to identify the subset of genes that were differentially expressed following a ten-month period of exercise training. The study cohort comprised seven Thoroughbred racehorses from a single training yard. Skeletal muscle biopsies were collected at rest from the gluteus medius at two time points: T1 - untrained, (9 ± 0.5 months old) and T2 - trained (20 ± 0.7 months old).ResultsThe m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 118 publications
6
59
0
5
Order By: Relevance
“…Currently, Illumina technologies are offering higher resolution and are relatively consistent with each other [20]. Nevertheless, the variations in GC content in our sequence data have been seen before [21] and are attributable to dinucleotide fragmentation sites, primer biases, and the protocol followed by the laboratory [22].…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Currently, Illumina technologies are offering higher resolution and are relatively consistent with each other [20]. Nevertheless, the variations in GC content in our sequence data have been seen before [21] and are attributable to dinucleotide fragmentation sites, primer biases, and the protocol followed by the laboratory [22].…”
Section: Discussionmentioning
confidence: 64%
“…Recent studies have identified PER3 to be upregulated in response to training in skeletal muscle from elite equine athletes [21,37]. It was reported that circadian and metabolic regulation is tightly interlocked at both physiological and molecular levels [52].…”
Section: Discussionmentioning
confidence: 99%
“…Signifi- cantly, higher expression of PER3 of horse after exercise supports the role of PER3 in circadian rhythms that may play an important role in sports performance and its importance to achieve the optimal athletic performance [10]. Both RT-PCR and real-time qRT-PCR were performed to clarify the qualitative and quantitative expressions of the genes under study.…”
Section: Resultsmentioning
confidence: 83%
“…Une étude transcriptomique comparée avant et après 10 mois d'entraînement a été réalisée en 2010 sur le muscle, montrant une diminution de l'expression de 58 gènes, dont le gène codant la myostatine (McGivney et al 2010), une protéine régulant négativement la masse musculaire. Une recherche de polymorphisme par séquen-çage du gène équin, ainsi qu'une analyse d'association pangénomique, ont montré qu'un polymorphisme C>T dans l'intron 1 du gène était associé aux aptitudes sportives : les chevaux C/C sont plus doués pour les courses rapides (sprinters), les individus T/T ont plus d'endurance et gagnent les courses de fond (stayers), alors que les hétérozygotes C/T peuvent être d'excellents milers.…”
Section: La Caractérisation Des Aptitudesunclassified